KONSEP PERLINDUNGAN HUKUM KORBAN PEMAKSAAN KEHAMILAN DALAM RUMAH TANGGA - Laiqah Nur Ahadiyati (2023)
Sexual violence is a forced sexual act committed by an adult against another person, which involves inappropriate sexual behavior. Domestic violence, according to the Law on the Elimination of Domestic Violence, refers to acts against a person, particularly women, resulting in physical, sexual, psychological suffering, and household neglect, including threats, coercion, or deprivation of freedom within the household context. Forced pregnancy is one form of domestic violence, specifically referring to cases where pregnancy is imposed without consent, rather than forced sexual intercourse. The purpose of this research is to examine how Indonesian law regulates forced pregnancy and to explore the legal protection concepts for victims of forced pregnancy in domestic settings. The research methodology employed in this study is normative juridical research is a research conducted by researching library materials, in this study based on the Annual Records of the National Commission on Violence against Women in 2020, 2021 and 2022. The approach to the problem used is a statutory approach and a conceptual approach. The findings indicate that existing laws have not clearly addressed forced pregnancy, resulting in limited application of sanctions against perpetrators of this criminal act. Legal protection concepts for victims of forced pregnancy could involve amending or revising the Law on the Elimination of Domestic Violence to incorporate provisions on forced pregnancy, establishing safe spaces for victims of violence, dedicated services to handle reports of violence, particularly forced pregnancy, raising awareness about reproductive health, forced pregnancy, and establishing a dedicated hotline for complaints, as well as prenuptial agreements addressing agreements on family planning programs.